2017
DOI: 10.3390/ijerph14090979
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Indoor Air Pollution and Childhood Allergies in Households in Six Chinese Cities by Subjective Survey and Field Measurements

Abstract: Greater attention is currently being paid to the relationship between indoor environment and childhood allergies, however, the lack of reliable data and the disparity among different areas hinders reliable assessment of the relationship. This study focuses on the effect of indoor pollution on Chinese schoolchildren and the relationship between specific household and health problems suffered. The epidemiological questionnaire survey and the field measurement of the indoor thermal environment and primary air pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 52 publications
(54 reference statements)
1
13
0
Order By: Relevance
“…Cooking and smoking were major indoor sources of PM 2.5 in homes in the UK [29,30] and USA [31]. In addition to indoor smoking [32,33], PM 2.5 levels were strongly influenced by the use of coal for cooking [34] and motor vehicle emissions [35] in China. The use of kerosene and biomass fuels for cooking increased indoor PM 2.5 concentrations to a level 7-fold greater than the World Health Organization (WHO) guidelines in Dhaka, Bangladesh [36].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cooking and smoking were major indoor sources of PM 2.5 in homes in the UK [29,30] and USA [31]. In addition to indoor smoking [32,33], PM 2.5 levels were strongly influenced by the use of coal for cooking [34] and motor vehicle emissions [35] in China. The use of kerosene and biomass fuels for cooking increased indoor PM 2.5 concentrations to a level 7-fold greater than the World Health Organization (WHO) guidelines in Dhaka, Bangladesh [36].…”
Section: Resultsmentioning
confidence: 99%
“…Forty-two studies reported indoor concentrations of one or more VOCs (excluding studies that only reported formaldehyde or other carbonyls). VOC levels in homes depended on many factors, such as the strength of emission sources, ventilation rates, and the indoor oxidative environment, which reflected differences in chemical use, building design and materials, occupant behaviour, and season (e.g., [32,73,74]). Reported VOC concentrations were generally higher indoors than outdoors, including for benzene, particularly in colder seasons due to reduced ventilation and the use of oil and gas heaters [75][76][77][78][79][80][81].…”
Section: Exposure Levels Sources and Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…As people's lifestyle changes [50] and environmental pollution aggravates [51], the therapy of allergic diseases is increasingly challenging and has become a serious disease threatening public health. Food allergies can occur in people of all ages, and high-risk groups are mainly infants and children.…”
Section: Discussionmentioning
confidence: 99%
“…The high performance liquid chromatography (HPLC) method was applied for the analysis of carbonyls compounds, and the gas chromatography/ mass spectrometry (GC/MS) was used for the analysis of VOCs. 46 Besides, due to the PM 2.5 and carbonyls could be affected by fumes generated during the cooking period, measurements therefore were not made during such periods. Additionally, we asked occupants not to clean their rooms prior to and during samplings, so as to keep the indoor environment in a typical daily state.…”
Section: On-site Measurements and Analysismentioning
confidence: 99%